Approval of Equal Rights and Gender Differences in Well-Being - Rafael Lalive; Alois Stutzer (Institute for the Study of Labor (IZA), 2004)
Women earn less than men but are not less satisfied with life. This paper argues that norms on the appropriate pay for women compared to men explain these findings. We take citizens? approval of an equal rights amendment to the Swiss constitution as a proxy for the norm that ?women and men shall have the right to equal pay for work of equal value?. We find that the gender wage gap narrows by one fifth due to an increase by one standard deviation in the approval. Rejecting an explanation in terms of discrimination, we find that employed women are less (not more) satisfied with life in liberal communities where the gender wage gap is smaller.
Keywords: Z13; J70; J16; I31; J31; 330; equal rights; gender discrimination; gender wage gap; social norms; subjective well-being; Lohndifferenzierung; Geschlechterdiskriminierung; Soziale Werte; Lebensqualität; Frauen; Schweiz; Lebenszufriedenheit